The Application of Aleatoric Technique through Graphic Notation in the Choral Composition “Acumalaka” - Gunawan, Sailendra Bedantara; Gunawan, Iwan; Saiful, Abizar Algifari (Fakultas Bahasa dan Seni UNP, 2024)
This article examines the use of aleatoric techniques through graphic notation in the choral music composition Acumalaka. It aims to demonstrate how aleatoric techniques and graphic notation can enhance artistic quality and musical expression. The composition process applied the practice-led research method, with the researcher serving as both composer and conductor. This approach involved the direct creation of the piece, alongside observing the choir's rehearsal and performance. Additionally, interviews with 14 singers were conducted to explore their experiences interpreting graphic notation and adapting to the creative freedom that aleatoric techniques allow. The collected data was analyzed thematically, combining critical reflections on the creative process with the singers' insights. Findings indicate that using aleatoric techniques through graphic notation enriched the musical dynamics, fostered creativity, and strengthened interactions among choir members. Moreover, aleatoric techniques and graphic notation can support innovative and collaborative musical experiences.